2020
DOI: 10.1097/prs.0000000000006463
|View full text |Cite
|
Sign up to set email alerts
|

Can You Trust What You Watch? An Assessment of the Quality of Information in Aesthetic Surgery Videos on YouTube

Abstract: Background: Videos on YouTube can be posted without regulation or content oversight. Unfortunately, many patients use YouTube as a resource on aesthetic surgery, leading to misinformation. Currently, there are no objective assessments of the quality of information on YouTube about aesthetic surgery. Methods: YouTube was queried for videos about the 12 most common aesthetic surgical procedures, identified from the 2015 American Society of Plastic Surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 20 publications
2
44
0
1
Order By: Relevance
“…Of all the medical specialties, plastic surgery is the one most present on social media [19] which might be in part due to the obvious visual component of plastic surgery. But overall the quality of videos posted to YouTube regarding a wider variety of plastic surgical topics is poor [20]. As our review showed there are currently only few publications about the educational value of YouTube for plastic surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Of all the medical specialties, plastic surgery is the one most present on social media [19] which might be in part due to the obvious visual component of plastic surgery. But overall the quality of videos posted to YouTube regarding a wider variety of plastic surgical topics is poor [20]. As our review showed there are currently only few publications about the educational value of YouTube for plastic surgery.…”
Section: Discussionmentioning
confidence: 89%
“…As vlogging (video logging) has increased in recent years, it is important to understand the quality, reliability, and influence of vloggers (video loggers) on consumers, especially among generation Z, with some vloggers having upwards of 100 million subscribers. 21 While there have been studies that have assessed the quality of information of YouTube videos on Botox, 15 plastic surgery, 16 and aesthetic surgical procedures, 17 there has been no such study analyzing both the source reliability and educational value of YouTube videos on neurotoxin procedures.…”
Section: Discussionmentioning
confidence: 99%
“…14 As a result, information contained within these videos can consist of unreliable or potentially inaccurate medical information that may pose a detriment to a patient's health and allure patients toward certain procedures. While there have been studies that have assessed the quality of information of YouTube videos on Botox, 15 plastic surgery, 16 and aesthetic surgical procedures, 17 there has been no such study analyzing both the source reliability and educational value of YouTube videos on neurotoxin procedures. In this study, we aim to assess the content, video characteristics, source reliability, and educational value of YouTube videos regarding neurotoxin treatments.…”
mentioning
confidence: 99%
“…On August 12, 2020, https://www.youtube.com was searched using the keywords “facial filler” or “dermal filler” or “filler.” Ranking option “relevance” was selected, and videos were reviewed in descending order as presented. Based on previously published research, 20,21 a total of 100 videos were initially reviewed for the following inclusion criteria: the video must discuss the usage of fillers in the face, must be primarily in English, and must be intended for patients. Videos that were non-English language, intended for medical professional education, or irrelevant to the topic of fillers were excluded from further analysis.…”
Section: Methodsmentioning
confidence: 99%